Beyond html - Karpinski, Richard (Osborne McGraw-Hill, 1996)
This book is the handbook for all Webmasters. It's a one-stop resource for those who want to unleash their creativity with their Web site, and are looking for just the right tools to enable them to do that. It provides much-needed information and direction on implementing the best of the new technologies and HTML alternatives created to improve Web sites. Sorting the contenders from the pretenders of these new technologies, it discusses how they work, and which are the best. The author also focuses on the key technology and gives a multi-chapter hands-on tutorial so that readers get up and running quickly.